The Pengaruh Literasi Wakaf, Media Online Dan Media Sosial Terhadap Niat Berwakaf Uang: studi pada mahasiswa Prodi Keuangan dan Perbankan Syariah Politeknik Negeri Medan - Ganda; Manik, M. Rikwan Effendi Salam; Wathan, Hubbul (Business Finance Analyst Co., 2025)
This study was conducted to determine the influence of waqf literacy, online media and social media on the intention to waqf study money in students of the Sharia Finance and Banking Study Program of the Medan State Polytechnic. In this study, there are independent variables, namely waqf literacy, online media, and social media, while dependent variables, namely the intention to waqf money. The sample used in this study was 75 respondents, namely students of the Sharia Finance and Banking Study Program, Medan State Polytechnic and used questionnaires as primary data. The questionnaire data collection technique was assessed using a Likert scale, validity test and reliability test. Prerequisite tests include normality tests, heteroscedasticity tests and multicollinearity tests. The data analysis technique to answer the hypothesis used multiple linear regression analysis, simultaneous test (F), determination test and partial test (t) with a significance level of 5% (α= 0.05) processed with the help of SPSS 25 software. The results of the partial test showed that the variable of waqf literacy was partially ineffectual and insignificant on the intention to waqf money with a significance level of 0.418, the variable of online media was influential and significant to the intention of waqf money with a significance level of 0.002 and the social media variable was partially influential and significant on the intention to waqf money with a significance level of 0.020. Simultaneously, the variable influence of waqf literacy, online media and social media had an effect and significance on the intention to waqf study money in students of the Sharia Finance and Banking Study Program at the Medan State Polytechnic with a significance level of 0.000 .